Parasites Prevalence of Dairy Cattle in Argopuro Area, Krucil District, Probolinggo Regency, Indonesia - Pradana, Giffari Danindra; Mufasirin; Madyawati, Sri Pantja; Tri Suwanti, Lucia; Kusnoto; Sunarso, Agus; Aryaloka, Suhita (Veterinary Biomedical and Clinical Journal, 2023)
This study aimed to identify endoparasitic species and their prevalence in dairy cows in the Probolinggo, Indonesia. This survey was conducted in the Cooperation of Argopuro, in the hill side of Krucil district, Probolinggo regency, during rainy season from March until July 2020. Faecal samples were collected (n=100), and three fecal examinations were performed for parasite identification: native, sedimentation, and flotation techniques. Results showed that the prevalence of endoparasitosis was 56%; 29% was due to helminthiases and the other 37% was of Balantidium coli. Fasciola sp., Oesophagostomum sp., Gaigeria pachyscelis, Toxocara vitulorum, Mecistocirrus digitatus, Chabertia sp. were among the helminths detected. The Lucient Brump test indicated that among samples infected with helminths (n=29), 89.7% were mild, 6.9% were moderate and 3.4% were severely infected. Further, the study estimated that the level of burden with Balantidium coli was identified to be mild in 62.2%, moderate in 32.4%, and severe in 5.4% of the positive samples, respectively (n=37). This study indicates that during the commencement of the rainy season, the campaign of effective endoparasitic control could be advisable in the study area